FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PARIWISATA KE INDONESIA ANALISIS DATA PANEL 21 NEGARA KUNJUNGAN WISATAWAN ASINGPERIODE 2006-2012 - , AMELIA PUTRI, Dra Endang Sih Prapti, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tourism is a commodity that has an important role in the Indonesian economy is as a source of non-oil revenues are the largest foreign exchange . This study aims to examine the factors that affect demand for Indonesian tourism which is illustrated by the number of foreign tourist arrivals . Factors affecting the number of foreign tourists is the price of tourism , the country's national tourist income , exchange rate Rupiah against foreign tourists currencies, and geographical distance between Indonesia and the country of origin of tourists. Tourism is a commodity that is prone to be influenced by external factors that unexpected or unpredictable influences. Therefore, in addition to the above factors , this study also examines the effect of the financial crisis . This study uses panel data analysis of cross - section . Results obtained using random effects panel data models claim that the price of tourism , the national income of the country of origin of tourists, exchange rate Rupiah against foreign tourists currencies, the geographical distance between Indonesia and the country of origin of tourists, and the world financial crisis which is happened in 2009 significantly affect the number of tourist visit to Indonesia. Keywords: tourism demand, tourism price, national income, exchange rate, geographically distance, financial crisis, random effect.